Effectiveness of an app-based walking program for obese patients with inflammatory bowel disease in Korea: a single-blind parallel-group randomized clinical trial - Young Jin Lee; Eun Ja Kwon; Da-In Park; Sang Hyoung Park; Sung Wook Hwang; Byong Duk Ye (BMC Gastroenterology)
Abstract Background Obesity in patients with inflammatory bowel disease (IBD) not only exacerbates symptoms but also interferes with treatment and leads to additional complications. Therefore, managing weight loss and preventing obesity are crucial. This study was designed to develop and implement a 10-week walking exercise program, facilitated by a mobile application, to evaluate its effectiveness in managing weight in obese IBD patients. Methods This study was designed as a single-blind parallel-group randomized clinical trial. We enrolled 54 participants, randomly allocating 27 to the intervention group and 27 to the control group. The intervention group received educational materials, such as videos, and participants were instructed to walk a minimum of 7,000 steps on at least five days each week for a duration of 10 weeks. Additionally, they were required to submit weekly updates on weight-related information to the researchers. The primary outcomes measured were body mass index (BMI), body fat percentage, and skeletal muscle mass. Secondary outcomes included perceived stress, fatigue, and quality of life. Results A total of 49 participants were included in the data collection (intervention group: n = 24, control group: n = 25). Post-intervention, the intervention group demonstrated significant reductions in BMI (t = 3.57, p =.001) and body fat percentage (Z = 3.11, p =.002) compared to the control group. Furthermore, perceived stress (t = 2.20, p =.038) and fatigue (t = 2.10, p =.047) significantly decreased in the intervention group, but no significant differences were observed when compared to the control group. Conclusions The 10-week walking program utilizing a mobile app effectively reduced body fat among participants, indicating its potential to improve health management in clinical settings. Further research is necessary to explore changes in muscle mass and psychological variables. Trial registration Korea Clinical Trials Registry number KCT0009461, 24/05/2024.